Uji Ketahanan Penyakit Antraknosa yang Disebabkan oleh Colletotrichum Gloesporioides pada Populasi (M3) Cabai Lokal Aceh - Siti Hafsah; Nura Nura; Firdaus Firdaus; Putri Amelia (Jurnal Agrotek Lestari, 2022)
This research aimed to determine the level of resistance of the mutant genotype against anthracnose caused by Colletotrichum gloeosporioides in the M3 population of local Aceh chilies as a result of gamma irradiation. The experimental design used in this study was a non-factorial randomized block design (RAK) with three replications and 17 observation parameters. The factors studied included one local Aceh variety (Odeng) as the parent, four mutant genotypes (M3) with various levels of gamma ray irradiation doses and two national varieties (Kastilo and Laris) as comparisons. The results showed that the quantitative character of the D1-10-5 mutant genotype was the best on the parameters of fruit length, number of fruits per plant, fruit weight per plant and plant productivity. The best D2-7-39 genotype on dichotomous height parameters, peroxidase enzyme activity in healthy leaves and peroxidase enzyme activity in sick leaves. The best D3-9-9 genotype on parameters of plant height, fruit diameter, weight per fruit, incidence of green fruit disease, intensity of green fruit disease and disease leaf peroxidase enzyme activity. The best genotype D3-9-34 on parameters of thickness of fruit flesh, incidence of red fruit disease, intensity of red fruit attack. The qualitative character of the young fruit color in the mutant genotypes D2-7-39, D3-9-34 and D3-9-9 gave rise to different characters from the elder varieties (odeng) and the comparison varieties of Castile and Laris, namely Dark Yellowish Green (3707). ). The color character of the intermediate fruit genotypes D1-10-5 and D3-9-34 produced a different color from the parent, namely Dark Redd Purple (9210).